Exploration exogenous factor of exchange rate: Data from Indonesia - Sulih Tiara Safitri; Nisa Mutiara; Eni Srihastuti (Jurnal Inovasi Ekonomi, 2021)
This study aimed to determine the relationship between remittance of Indonesian workers, gross domestic product and foreign exchange reserves to the exchange rate of IDR/USD in the period 2013-2017. This research is quantitative research with regression analysis. The data collection technique uses secondary data of Indonesian labor remittance reports, GDP, foreign exchange reserves, and the rupiah's exchange rate against the dollar for the 2013-2017 period. The analysis of the results shows a significant relationship between remittance and the exchange rate; there is no significant negative correlation between GDP and the exchange rate and there is no significant positive relationship between Foreign Exchange Reserves and the exchange rate.